Changes in Liver Shear Wave Elastography of Preterm Infants during Hospitalization - Kemmotsu, Takahiro; Shimokaze, Tomoyuki; Morita, Yusuke; Saito, Tomoko; Toyoshima, Katsuaki (American Journal of Perinatology, 2024)
Liver evaluation is essential in preterm infants because of exposure to hepatotoxic drugs, the effects of parenteral nutrition, and their organ immaturity. The clinical significance of shear wave elastography (SWE) which measures tissue elasticity, is unclear in preterm infants. For SWE application to liver evaluation in preterm infants, we examined the postnatal course and factors associated with changes.We prospectively measured liver SWE values every other week in 37 preterm infants born at 23 to 35 weeks gestation and 12 term infants born after 36 weeks gestation.The median early postnatal liver SWE value was 1.22 (interquartile range, 1.19–1.26) m/s. The correlations of liver SWE values with gestational age and birth weight were r = −0.18 (p = 0.23) and r = −0.21 (p = 0.157), respectively. The median liver SWE values from birth to 36 to 38 postmenopausal weeks were 1.22 (1.17–1.24) m/s at <28 weeks gestation (n = 9), 1.21 (1.18–1.25) m/s at 28 to 29 weeks gestation (n = 11), 1.24 (1.21–1.28) m/s at 30 to 31 weeks gestation (n = 8), and 1.21 (1.20–1.24) m/s at ≥32 weeks gestation (n = 9). There was no change over time in any gestational age group (p = 0.158). The median liver SWE values were 1.22 (1.17–1.25) m/s (n = 10) and 1.22 (1.19–1.25) m/s (n = 27) for small- and appropriate-for-gestational-age infants, respectively (p = 0.93). The correlations of abnormally high serum concentrations of direct bilirubin (>1.0 mg/dL) and alanine aminotransferase (>12 IU/L) with liver SWE values were r = 0.37 (p = 0.041) and r = 0.21 (p = 0.35), respectively.Liver SWE values may be useful for the evaluation of liver damage with cholestasis in preterm infants because they remain constant regardless of gestational age and birth weight and do not change over time or with a deviation of body size.
Keywords: acoustic radiation force impulse imaging; preterm infant; cholestasis; liver stiffness; small for gestational age